Ontology Development for Library Science Taxonomy Based on Facet Categorization - Pornprasit, Chayanon; Vadhanasin, Vipakorn (Journal of Information Technology and Innovation, 2023)
The purposes of this study were to 1) develop an ontology of library science terminology by facet classification and 2) to evaluate an ontology of library science terminology. Data were collected from search terms in library database by selecting 320 library science related words. The ontology was developed by content analysis to define knowledge structures and group terms using facet classification. The knowledge was divided into 12 domains as follows: 1) intellectual property 2) library and information science career 3) information sources 4) knowledge management 5) information resources 6) social media 7) classification 8) archives 9) library’s tasks 10) librarian professional associations 11) search tools and 12) digital libraries. The ontology consisted of 44 main classes, 243 subclasses, 4 types of 13 hierarchical relationships, and 39 instances. The ontology was evaluated using a Delphi technique by 9 experts to validate the classification and structure of the ontology, including the completeness and relationships within the structure. It was found that, on average, the completeness was at the highest level ( =4.78), the consistency was at the highest level ( =4.78), the conciseness was at a high level ( =4.44), the accuracy was at the highest level ( =4.85) and the clarity was at the highest level ( =4.78).